2017
DOI: 10.1080/17408989.2017.1371684
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the relationships between the teaching climate, students’ perceived life skills development and well-being within physical education

Abstract: Background: Both education policies and curriculum documents identify the personal development of students as a key objective of modern education. Physical education in particular has been cited as a subject that can promote students' life skills development and psychological well-being. However, little research has investigated the processes by which physical education may be related to students' development of life skills and their psychological well-being. Purpose: Using Benson and Saito's (2001) framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 49 publications
9
52
0
9
Order By: Relevance
“…31 Research within physical education has also shown that students' total life skills development within physical education is consistently associated with their psychological well-being. 25 These findings fit with the untested premise that the more life skills young people learn through sport, the more likely they will develop in a positive manner. 32 In their framework for youth development theory and research, Benson and Saito 1 proposed that youth development inputs (e.g., the coaching climate) serve to develop young peoples' strengths (e.g., their life skills), and the development of these strengths promote other well-being outcomes.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…31 Research within physical education has also shown that students' total life skills development within physical education is consistently associated with their psychological well-being. 25 These findings fit with the untested premise that the more life skills young people learn through sport, the more likely they will develop in a positive manner. 32 In their framework for youth development theory and research, Benson and Saito 1 proposed that youth development inputs (e.g., the coaching climate) serve to develop young peoples' strengths (e.g., their life skills), and the development of these strengths promote other well-being outcomes.…”
Section: Introductionsupporting
confidence: 64%
“…Specifically, the findings from this study confirmed the results of a review paper 16 , which reported that young people perceive they develop the following life skills through sport: teamwork, goal setting, time management, emotional skills, interpersonal communication, social skills, leadership, and problem solving and decision making. When compared to the research in physical education, 25 it seems that youth sport participants perceive they develop the same eight life skills, but to a greater extent than students within physical education classes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, recent academic attention has turned to the ways in which youth sport (Jacobs & Wright, ) and mainstream PE (e.g. Cronin, Allen, Mulvenna, & Russell, ) can facilitate the development of life skills, something that may be essential for helping CYP with intellectual disabilities to live with greater independence once they leave compulsory education. Nonetheless, it is important to note that access to these opportunities will be determined by associated costs and the availability of appropriate transport.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown a positive relationship between the satisfaction of the BPN and self-determined motivation [13,[22][23][24], as well as between more self-determined motivation and autotelic experience [25][26][27]. Similarly, it has been shown that a climate of support for autonomy is beneficial for students, as it increases their perception of autonomy [28,29]; is related to the satisfaction of the BPN [30][31][32]; produces benefits in motivation and well-being [33]; and increases enjoyment in PE classes [34,35] and the development of life skills [36], thus favouring self-determined motivation and the intention to continue carrying out physical activity [18].…”
Section: Introductionmentioning
confidence: 99%